(3GdbhGYO aj Yde GdcdGes
(3ChdgG (B:s
(3Chd GdehLhO CKfGA GdbGYOI GdKGfjI hChd GdbGYOI GdKGdKI ai GdJhMjO s
(3BNQgG (B:s
(3jfJgi HCKfGA GdbGYOI GdYTQjf ai EKHGJ fHhI fHjfG Ydjg GdSdGe s
(3GdcJGH ebSe Edi YTQjf bGYOIs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJhMjO hGdedd hGdfMds